Do conventional monetary policy instruments matter in unconventional times? - Manuel Buchholz; Kirsten Schmidt; Lena Tonzer (Deutsche Bundesbank, 2019)
This paper investigates how declines in the deposit facility rate set by the ECB affect euro area banks' incentives to hold reserves at the central bank. We find that, in the face of lower deposit rates, banks with a more interest-sensitive business model are more likely to reduce reserve holdings and allocate freed-up liquidity to loans. The result is driven by wellcapitalized banks in the non-GIIPS countries of the euro area. This reveals that conventional monetary policy instruments have limited effects in restoring monetary policy transmission during times of crisis.
Keywords: E52; G11; G21; 330; bank portfolio; central bank reserves; monetary policy